2008
DOI: 10.1108/10610420810896059
|View full text |Cite
|
Sign up to set email alerts
|

Investigating antecedents and consequences of brand identification

Abstract: Original article can be found at: http://www.emeraldinsight.com/ Copyright Emerald [Full text of this article is not available in the UHRA]Purpose - This study aims to analyse the influences of prestige, satisfaction, and communication on brand identification and to show how brand identification influences word-of-mouth and brand repurchase. Design/methodology/approach - A theoretical model is developed and tested with a sample of car owners in the UK of two global car brands. Structural equation modelling was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
212
4
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(256 citation statements)
references
References 64 publications
22
212
4
18
Order By: Relevance
“…The branding literature increasingly emphasizes brand identity as a dynamic process which develops over time (da Silveira, Lages, & Simões, 2013;StokburgerSauer, Ratneshwar, & Sen, 2012). Recently, the application of a social identity perspective highlights a pivotal role of brand identification in the process of brand loyalty development (He, Li, & Harris, 2012;Kuenzel & Halliday, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The branding literature increasingly emphasizes brand identity as a dynamic process which develops over time (da Silveira, Lages, & Simões, 2013;StokburgerSauer, Ratneshwar, & Sen, 2012). Recently, the application of a social identity perspective highlights a pivotal role of brand identification in the process of brand loyalty development (He, Li, & Harris, 2012;Kuenzel & Halliday, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ahearne, Bhattacharya, and Gruen's (2005) study on customer-company identification indicated that the more the customers identify with a company the greater the impact on purchasing behavior. Similarly, Kuenzel and Halliday's (2008) study with a sample of car owners in the UK found brand identification plays a significant mediating role in the relationships between prestige, satisfaction, and communication and word of mouth and brand repurchase. The findings of Carlson et al's (2009) study in the sport context also revealed that a consumer's identification with the sport team brand had a positive impact on the number of games that fans watched and the amount of money spent on team-related retail purchases.…”
Section: The Influence Of Brand Identification On Intention To Returnmentioning
confidence: 99%
“…While employees' organizational identification has been studied previously (Jones 2010, De Roeck andDelobbe 2012), consumers' attitudinal and behavioral responses toward brand identification require more research. Investigators believe that a better understanding of the concept of brand identification would provide deeper insights into brand management (Kuenzel and Vaux Halliday 2008), and suggest that strong brand identification can result in favorable responses of consumers toward the brand, including brand loyalty (Donavan et al 2006).…”
Section: Fatma and Rahman: Perceived Ethicality Influences On Brand Lmentioning
confidence: 99%